Alternative Penalties for Imprisonment in Islamic Jurisprudence and its Contemporary Forms in the Bahrain Penal Code and Alternative Measures No. 18 of 2017 - Busaeed , Salman Duaij (Dirasat: Shari'a and Law Sciences, 2021)
Alternative penalties are modern legislative trends to replace imprisonment with alternative penalties that contribute to integrating prisoners into society and keeping them away from crime and its ways. This research investigates alternative penalties and their legal provisions on the one hand, and addresses the types of alternatives to imprisonment in Islamic jurisprudence and its contemporary forms in Bahraini Law No. 18 of 2017, in addition to the restrictions on its application, on the other. The research followed the inductive method by extrapolating the texts of jurists in the definition of alternative penalties, their rulings, and images in Islamic jurisprudence and the descriptive method by describing the importance of alternative penalties, their contemporary images and controls to implement them. The research concluded that alternative penalties are measures and reform measures taken by the state or its representatives that serve as an alternative to imprisonment to prevent the recurrence of crime and reduce it in society, and aim to reduce the number of detainees and integrate them into society. The most important forms of alternative penalties to imprisonment in Islamic jurisprudence appear in flogging, financial fines, exile, alienation, summons, reprimand and desertion, and contemporary forms of community service, house arrest or the ban on going to specific places, electronic monitoring, attending rehabilitation programs, and repairing the damage resulting from the crime. The research suggests that alternative penalties for imprisonment be applied provided that they are suitable to the felony committed, and that it does not harm the perpetrator or society..